The Fibrin Assay Comparison Trial (FACT): Correlation of Soluble Fibrin Assays with D-dimer - Dempfle, Carl-Erik; Zips, Sybille; Ergül, Hanimsah; Heene, Dieter L.; the FACT study group (Thrombosis and Haemostasis, 2001)
Soluble fibrin (SF) is regarded as an indicator of acute fibrin formation and a precursor of fibrin thrombi. Using a set of clinical plasma samples, and fibrin derivatives, five assays for measurement of SF, including two chromogenic assays, two ELISA systems, and one latex-enhanced photometric immunoassay were compared. Correlation between SF assays was moderate (Spearman’s rho values between 0.344 and 0.805). Re-calibration with serial dilutions of desAABBfibrin monomer resulted in adjustment of the numerical scale of the assays without improving correlation.All SF assays reacted with purified crosslinked fibrin derivatives. Using clinical plasma samples, Spearman’s rho of SF assays with D-dimer consensus values based upon results of 23 quantitative D-dimer assays were between 0.491 and 0.911.Although all SF assays react with desAABB-fibrin monomer complexes, SF assays are heterogeneous concerning reactivity with fibrin compounds observed in clinical plasma samples. The prospect of a common calibrator for SF assays therefore seems to be remote.Since SF assays react with crosslinked fibrin derivatives, it is not possible to clearly distinguish between acute fibrin formation, and fibrin dissolution on the basis of the results of current SF assays.
Keywords: Fibrin; fibrinogen degradation products; fibrin monomer; assay; standardization